Development of 3-phase inverter with PID voltage control - Ahmad Rebudi, Muhammad Faddil (2014)
The inverter converts electrical signal from DC to AC by using power electronic circuits. Inverter output is square waves and a filter is needed to change the output to a sinusoidal wave. A control method is implemented in this project to create stable sinusoidal voltage amplitude. The benefit of using control method is the inverter can be adjusted to adapt to a variety of loads and able to mitigate any small disturbance in the system. PID controller is chosen for this project because the PID controller can solve a very complex control for nonlinear element. The PID controller is developed in Matlab Simulink simulation and coded into TMS320F28335 board. In TMS320F28335 board, the desired voltages are compared with the output voltages to get the error signal that will go into the PID controller. SPWM signal is created by using the correction signal from PID controller and fed to the three-phase inverter with filter to give a sinusoidal output. Based on the result obtained, the three-phase inverter has successfully created a stable sinusoidal voltage output for any given 3 voltage 7 references 7 by utilizing $ the ADC module and the PID controller. 3(53867$.$$1781.878